The effect of structural disorder on the hydrogen loading into the graphene/nickel interface. (31st October 2022) - Petrone, Gaetana; Zarotti, Francesca; Lacovig, Paolo; Lizzit, Daniel; Tosi, Ezequiel; Felici, Roberto; Lizzit, Silvano; Larciprete, Rosanna
Abstract: Hybrid materials composed by porous Ni foams coated by graphene appear appealing architectures to be applied in the field of hydrogen storage, where, due to the high surface-to-volume ratio of both components, are expected to be much more performant than their flat counterparts. In order to explore this possibility, in this study we have grown single layer graphene on nickel foams by chemical vapour deposition in ultra-high vacuum and have investigated the interaction with H atoms as a function of the temperature. By using high resolution C1s core level spectroscopy we found that nearly half of the graphene layer interacts with the support almost as strongly as with the flat ordered Ni substrate, whereas the other half is nearly free standing. Such dual electronic and structural coupling drives the hydrogenation of the graphene/foam interface. By using thermal programmed desorption combined with x-ray photoelectron spectroscopy we found that in the weakly interacting graphene regions, even at very low temperatures, H atoms easily intercalate below graphene, and enter in the bulk of the foam, from where they start to desorb around 180 K. This behaviour mimics what happens when dosing H atoms on the bare Ni foam. On the contrary, H intercalation below the strongly interacting graphene regions occurs only for temperatures around and above 200 K. The thermal desorption curves demonstrated that the presence of the graphene layer does not reduce the effectiveness of H loading in the bulk of the foam. On the other hand, it does not even increase significantly the stored amount with respect to the uncoated support, but contributes to stabilizing the stored hydrogen. Although the fundamental aspects of graphene/foam hydrogenation were here investigated in a regime far below the saturation of the bulk absorption, these measurements can be the starting point for further investigations aimed at establishing the ultimate storage capability of these hybrid nanostructured tanks. Graphical abstract: Image 1